Iron accumulation typifies renal cell carcinoma tumorigenesis but abates with pathological progression, sarcomatoid dedifferentiation, and metastasis - Greene, Christopher J.; Attwood, Kristopher; Sharma, Nitika J.; Balderman, Benjamin; Deng, Rongia; Muhitch, Jason B.; Smith, Gary J.; Gross, Kenneth W.; Xu, Bo; Kauffman, Eric C. (Frontiers in Oncology, 2022)
Iron is a potent catalyst of oxidative stress and cellular proliferation implicated in renal cell carcinoma (RCC) tumorigenesis, yet it also drives ferroptosis that suppresses cancer progression and represents a novel therapeutic target for advanced RCC. The von Hippel Lindau (VHL)/hypoxia-inducible factor-α (HIF-α) axis is a major regulator of cellular iron, and its inactivation underlying most clear cell (cc) RCC tumors introduces both iron dependency and ferroptosis susceptibility. Despite the central role for iron in VHL/HIF-α signaling and ferroptosis, RCC iron levels and their dynamics during RCC initiation/progression are poorly defined. Here, we conducted a large-scale investigation into the incidence and prognostic significance of total tissue iron in ccRCC and non-ccRCC patient primary tumor cancer cells, tumor microenvironment (TME), metastases and non-neoplastic kidneys. Prussian Blue staining was performed to detect non-heme iron accumulation in over 1600 needle-core sections across multiple tissue microarrays. We found that RCC had significantly higher iron staining scores compared with other solid cancers and, on average, >40 times higher than adjacent renal epithelium. RCC cell iron levels correlated positively with TME iron levels and inversely with RCC levels of the main iron uptake protein, transferrin receptor 1 (TfR1/TFRC/CD71). Intriguingly, RCC iron levels, including in the TME, decreased significantly with pathologic (size/stage/grade) progression, sarcomatoid dedifferentiation, and metastasis, particularly among patients with ccRCC, despite increasing TfR1 levels, consistent with an increasingly iron-deficient tumor state. Opposite to tumor iron changes, adjacent renal epithelial iron increased significantly with RCC/ccRCC progression, sarcomatoid dedifferentiation, and metastasis. Lower tumor iron and higher renal epithelial iron each predicted significantly shorter ccRCC patient metastasis-free survival. In conclusion, iron accumulation typifies RCC tumors but declines toward a relative iron-deficient tumor state during progression to metastasis, despite precisely opposite dynamics in adjacent renal epithelium. These findings raise questions regarding the historically presumed selective advantage for high iron during all phases of cancer evolution, suggesting instead distinct tissue-specific roles during RCC carcinogenesis and early tumorigenesis versus later progression. Future study is warranted to determine how the relative iron deficiency of advanced RCC contributes to ferroptosis resistance and/or introduces a heightened susceptibility to iron deprivation that might be therapeutically exploitable.